Translational Entropy and DNA Duplex Stability - Privalov, Peter L. (Biophys J, 2018)
Investigation of folding/unfolding DNA duplexes of various size and composition by superprecise calorimetry has revised several long-held beliefs concerning the forces responsible for the formation of the double helix. It was established that: 1) the enthalpy and the entropy of duplex unfolding are temperature dependent, increasing with temperature rise and having the same heat capacity increment for CG and AT pairs; 2) the enthalpy of AT melting is greater than that of the CG pair, so the stabilizing effect of the CG pair in comparison with AT results not from its larger enthalpic contribution (as expected from its extra hydrogen bond), but from the larger entropic contribution of the AT pair that results from its ability to fix ordered water in the minor groove and release it upon duplex unfolding; 3) the translation entropy, resulting from the appearance of a new kinetic unit on duplex dissociation, determines the dependence of duplex stability on its length and its concentration (it is an order-of-magnitude smaller than predicted from the statistical mechanics of gases and is fully expressed by the stoichiometric correction term); 4) changes in duplex stability on reshuffling the sequence (the “nearest-neighbor effect”) result from the immobilized water molecules fixed by AT pairs in the minor groove; and 5) the evaluated thermodynamic components permit a quantitative expression of DNA duplex stability.